DIABETES MELLITUS AND CARDIOVASCULAR COMPLICATIONS: FOCUS ON HEMOSTASIS - G. G. Petrik; S. A. Pavlishchuk; E. D. Kosmacheva (Российский кардиологический журнал, 2014)
This literature preview presents modern evidence on the mechanisms of prothrombotic status development in diabetes mellitus, taking into consideration the association between metabolic disturbances, increased functional platelet activity, and hemocoagulation.